1 ) ( k + 5 ) * 7 - 54 = ( k + 5 ) * 4 ; 7 * ( k + 5 ) -54= 4 * ( k + 5 ) ; 7 * k + 7 * 5 - 54 = 4 * k + 4 * 5 ; 7 * k + 35 - 54 = 4 * k + 20 ; 7 * k - 4 * k = 20 - 35 + 54 ; k * ( 7 - 4 ) = 20 - 35 + 54 ; 3 * k = - 15 + 54 ; 3 * k = 39 ; k = 39 / 3 ; k = 13 * 3 / 3 ; k = 13 / 1 ; k = 13 ;2 ) 17 * ( c - 2 ) - 36 = 19 + ( c - 2 ) * 12 ; 17 * c - 17 * 2 - 36 = 19 + 12 * c - 12 * 2 ; 17 * c - 34 - 36 = 19 + 12 * c - 24 ; 17 * c - 70 = 19 + 12 * c - 24 ; 17 * c - 70 = 12 * c - 5 ; 17 * c - 12 * c = - 5 + 70 ; 5 * c = 65 ; c = 65 / 5 ; c = 13.